Risk-taking during wayfinding is modulated by external stressors and personality traits. Issue 4 (2nd October 2019) - Brunyé, Tad T.; Martis, Shaina B.; Hawes, Breanne; Taylor, Holly A.
ABSTRACT: Two experiments examined cue reliance and risk-taking during desktop virtual wayfinding, and how they might be modulated by personality traits and external stressors. Participants navigated a series of virtual buildings and we manipulated the strength of probabilistic cues available to guide turn decisions. Navigators frequently discounted probabilistic cues and instead took risks, particularly when costs were low and potential benefits were high. Risk-taking was predicted by higher sense of direction and lower need for structure. Introducing a time stressor lowered risk-taking, with a higher relative reliance on probability-based information. This was most pronounced in females and those with a high need for structure. Results provide novel evidence that spatial cue reliance is modulated by individual differences and contextual constraints.